2011
DOI: 10.1055/s-0031-1274513
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Compression and Cross Clamping in a Case of Placenta Percreta and Amniotic Fluid Embolism: A Case Report

Abstract: Amniotic fluid embolism (AFE, also known as anaphylactoid syndrome of pregnancy) at the time of surgery for placenta percreta has been previously reported. We report here a case in which AFE and associated cardiac arrest occurred following a hysterectomy for placenta percreta. In this case, subhepatic manual aortic compression during the cardiac arrest and chest compressions followed by infrarenal aortic cross-clamping during volume infusion and reversal of the coagulopathy were associated with a successful re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
(14 reference statements)
0
9
0
Order By: Relevance
“…The blood flow in these anastomotic channels is preserved by maintaining blood pressure while the aorta is clamped 13 . The duration for which the aorta can be clamped safely has been reported as 90–150 min 7,8,13,14 . A recent animal study found reduced tensile strength of the aortic wall without any histologic changes after 60 min of cross clamping 15…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The blood flow in these anastomotic channels is preserved by maintaining blood pressure while the aorta is clamped 13 . The duration for which the aorta can be clamped safely has been reported as 90–150 min 7,8,13,14 . A recent animal study found reduced tensile strength of the aortic wall without any histologic changes after 60 min of cross clamping 15…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent placental adhesive disease has been reported in 30% of subsequent pregnancies 6 . A few case reports have found satisfactory hemostasis with aortic cross clamping during hysterectomy for placenta percreta 7–9 …”
Section: Introductionmentioning
confidence: 99%
“…We do recognize that there is a failure rate of internal iliac ligation and that it can be unsuccessful at stopping hemorrhage in some cases [ 16 ]. In this subset of patients, one may consider internal aortic compression as a means of temporizing blood loss while hysterectomy is performed [ 17 ]. In this patient, she did have significant blood loss documented at 2.5L, but much of the blood loss occurred prior to the hysterectomy from the area of rupture and can be attributed to the preexisting intraabdominal hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…52,54 In the nonarrest population, manual LUD compared with 15° left lateral tilt has been shown to result in less hypotension and a significantly lower ephedrine requirement during a cesarean delivery. 55 Additional benefits of manual LUD over tilt include easier access for both airway management and defibrillation. While manual LUD is performed, the patient can remain supine and receive usual resuscitative measures, including high-quality chest compressions without hindrance (Figure 3).…”
Section: Adult Chest Compression Sciencementioning
confidence: 99%
“…The vertical incision also opens the abdomen for manual compression of the aorta, which has been described as a lifesaving temporizing maneuver for women with catastrophic pelvic hemorrhage. 55 Both hyperkalemic and hypocalcemic arrest are best treated with calcium chloride and chest compressions. In addition, hyperkalemia should be treated with drugs that shift potassium into cells (eg, sodium bicarbonate, insulin and dextrose, and a β2-agonist),…”
mentioning
confidence: 99%